Socialization of Information: A New Research Agenda - Guimaraes, Maria Cristina S. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Summing up the two sides of the event information, information as a process and information as a product, Socialization of Information has emerged as a methodological perspective to bring about fresh insights on information themes. Focusing on human and social aspects of information transfer, Socialization of Information seeks to provide successful alternatives, which might improve. . .